Ground resource optimization for navigation constellation based on satellite link scheduling. Issue 4 (3rd April 2019) - Zhang, Tianjiao; Li, Jing; Yang, Yikang; Li, Hengnian; Li, Jisheng; Li, Zexi
ABSTRACT: The Global Navigation Satellite System (GNSS) provides autonomous geospatial positioning and time synchronization services for civilian and military purposes. GNSS satellite links are used to transmit signals for constellation management and other applications. To minimize the number of stations required in participant ground-based management and reduce management costs in the GNSS network, this study solves the satellite link scheduling problem over the dynamic satellite network, including the hybrid and fast-varying inter-satellite link (ISL) working system. Firstly, the management problem is divided into two phases. Secondly, a two-level solving scheme is designed according to the characteristics of the scheduling problem. Finally, a performance analysis of different scenarios is conducted. The experimental results show that the hybrid ISL working system provides more effectively utilized data transmitting bandwidth of satellite links, thereby reducing the use of ground-based management resources. This study provides a technical reference for the management of future large-scale satellite networks.